Modulatory Effects of Lycopene and Ellagic Acid on Reproductive Dysfunction Induced by Polychlorinated Biphenyl (Aroclor 1254) in Male Rats - Atessahin, Ahmet; Turk, Gaffari; Yilmaz, Seval; Sonmez, Mustafa; Sakin, Fatih; Ceribasi, Ali Osman (Wiley, 2010)
The present study was conducted to investigate the possible protective effects of lycopene (LP) and ellagic acid (EA) on aroclor (AR) 1254-induced testicular and spermatozoal toxicity associated with the oxidative stress and apoptosis in male rats. The control group was treated with placebo. LP (10 mg/kg/every other day), EA (2 mg/kg/every other day) and AR (2 mg/kg/day) groups were given alone LP, EA and AR respectively. One of the last two groups received AR + LP, and the other treated with AR + EA. Body and reproductive organ weights, epididymal sperm characteristics, testicular tissue lipid peroxidation levels, antioxidant enzyme activities, histopathological changes and apoptosis via Bax and Bcl-2 genes were investigated. AR administration caused statistically significant decreases in body-weight, epididymal sperm concentration, testicular superoxide dismutase activity, diameters of seminiferous tubules, germinal cell layer thickness and Johnsen's testicular score, and increases in relative weights of testis, epidydimis and seminal vesicles, rates of abnormal sperm and apoptotic cell expression along with degeneration, desquamation and disorganization in spermatogenic cells, and interstitial oedema and congestion in testicular tissue. LP and EA treatments to AR-treated rats markedly decreased abnormal sperm rates, testicular thiobarbituric acid reactive substances level, and increased the glutathione (GSH) level, GSH-peroxidase, catalase activities and epidiymal sperm concentration as compared with the alone AR group. Additionally, the AR-induced histopathological damages were totally or partially recovered by LP or EA administrations respectively. AR damages the testicular tissue and spermatozoa by impairing the oxidant/antioxidant balance and by increasing the apoptotic spermatogenic cell rates. However, both LP and EA have modulator effects on AR-induced reproductive dysfunction in male rats.
Keywords: Induced Testicular Toxicity; Oxidative Stress; Steroidogenic Enzymes; Antioxidant System; Protective Role; Sperm Function; Ascorbic-Acid; Exposure; Apoptosis; Pcb